From the Evolut Pro to the Evolut FX self-expanding transcatheter aortic valve replacement systems: current status and future perspectives. (3rd July 2022) - Panagides, Vassili; Mesnier, Jules; Nuche, Jorge; Delarochellière, Robert; Paradis, Jean-Michel; Kalavrouziotis, Dimitri; Dumont, Eric; Mohammadi, Siamak; Rodes-Cabau, Josep
ABSTRACT: Introduction: Since the initial experience with the CoreValve (Medtronic, Minneapolis, Minnesota), there have been continuous iterations of this valve system in order to improve procedural success and reduce periprocedural complications. The Evolut Pro, Pro+, and FX are the latest generations of this transcatheter heart valve (THV). Areas covered: This review paper aims to analyze the main characteristics and clinical evidence about the Evolut Pro THV and summarize the main iterations of the newer generation Evolut FX valve system. Expert opinion: The Evolut Pro system has been associated with good clinical outcomes and excellent valve hemodynamic performance including reduced rates of paravalvular leaks. Technical enhancements to improve valve positioning, orientation, and vascular access have been implemented in the newer generation Evolut FX system.